TRANSFORMASI BAGAWADGITA DAIAM LAKON BISMA DAN DURNA GUGUR PADA PEWAYANGAN JAWA SURAKARTA (Bagawadgita Tranformation in the episude Death of Bisma and Durna on J avaness Surakarta puppetry ) - Subandi - (Gelar : Jurnal Seni Budaya, 2007)
Bagawadgita is a literary work f!i India which has been adapted into old  Javanese language with the title Gitaning Bagawan meaning Kidungan Gusti.  Bagawadgita has been adapted into ma'!} International la'!guages among others  English, Dutch, French, and regional languages such as old Javanese langllage which  later was transformed into pedalanganjiteratllre. Bagawadgita amstitutes phi/oJop~y  and art. Bagawadgita contains Kresna's teaching to Arjllna when the war ~l  Baratayuda was in progress. .Arfuna being one of commanders-in-chief of .Amarta  was doubtflll after having known that his enemies were pepunden / parents he  respected very mllch, teachers who had tallght him and his own relatives. As a  nobleman, .Arjuna actuallY had not been capable for differentiating dury, task and  service. .Arjuna still needed Kresnas advice when he was facing his enemies. In the  war f!i Baratayuda, pepunden, teachers, relatives were not taken into consideration.  The opponents faced were the enemies who had evil characters and belonged 10 Kurawa.  There was no choice in the war, to kill or being killed Life or death is the same. In  Baratqyuda, those who won led to the bonorable wqy in the world that is power,  cOllntry and richness; those who died were believed to go into Heaven. As God's  messenger for jllstice, a nobleman had to destroy greed existing in the enemy. As the  enemies were those who had provided great merit to him, a nobleman had to carry ota  his dllry and differentiate right and dury exactlY. The wise Kresna had ma'!} accurate  wqys in giving adoices so .Arjuna had strong enthllsiasm to destroy his enemies. In the  episode f!i the death of Bisma and Durna, .Arfuna was given mucb advice how to  lead to glory.Keywords: Bagawadgita, teaching, a nobleman's duty